Pemasaran Kebijakan Politik Luar Negeri Sebagai Diplomasi Presiden Jokowi Untuk Menarik Investor Asing di Indonesia - Baidawi Ahmad; Azarkasi Azarkasi (Kemudi, 2019)
This paper wants to explain about Foreign Policy Marketing as President Jokowi's diplomacy to attract foreign investors. As we know, the Indonesian state from a geographical aspect has a very large area consisting of hundreds or even thousands of islands and straits. But the extent of the Indonesian territory has not been balanced with economic development such as infrastructure in all regions of Indonesia. This study aims to analyze the policies of President Jokowi in inviting foreign investors to invest directly in Indonesia and see the effect of foreign direct investment on foreign direct investment (FDI) on economic growth in Indonesia. The method used in this research is Qualitative Descriptive. The results or findings of this study indicate that the Marketing of Foreign Political Policy conducted by President Jokowi to attract foreign investors in Indonesia is through the economic Diplomacy Way and providing legal certainty for Foreign Investors investing in Indonesia and Foreign Investment can improve Infrastructure in Indonesia.